Bortezomib inhibits chikungunya virus replication by interfering with viral protein synthesis. - Parveen Kaur; Laura Sandra Lello; Age Utt; Sujit Krishna Dutta; Andres Merits; Justin Jang Hann Chu (Public Library of Science (PLoS), 2020)
Chikungunya virus (CHIKV) is an alphavirus that causes a febrile illness accompanied by myalgia and arthralgia. Despite having re-emerged as a significant public health threat, there are no approved therapeutics or prophylactics for CHIKV infection. In this study, we explored the anti-CHIKV effects of proteasome inhibitors and their potential mechanism of antiviral action. A panel of proteasome inhibitors with different functional groups reduced CHIKV infectious titers in a dose-dependent manner. Bortezomib, which has been FDA-approved for multiple myeloma and mantle cell lymphoma, was further investigated in downstream studies. The inhibitory activities of bortezomib were confirmed using different cellular models and CHIKV strains. Time-of-addition and time-of-removal studies suggested that bortezomib inhibited CHIKV at an early, post-entry stage of replication. In western blot analysis, bortezomib treatment resulted in a prominent decrease in structural protein levels as early as 6 hpi. Contrastingly, nsP4 levels showed strong elevations across all time-points. NsP2 and nsP3 levels showed a fluctuating trend, with some elevations between 12 to 20 hpi. Finally, qRT-PCR data revealed increased levels of both positive- and negative-sense CHIKV RNA at late stages of infection. It is likely that the reductions in structural protein levels is a major factor in the observed reductions in virus titer, with the alterations in non-structural protein ratios potentially being a contributing factor. Proteasome inhibitors like bortezomib likely disrupt CHIKV replication through a variety of complex mechanisms and may display a potential for use as therapeutics against CHIKV infection. They also represent valuable tools for studies of CHIKV molecular biology and virus-host interactions.